Analysis of Long-Term Temperature Trend as an Urban Climate Change Indicator - Dadang Subarna (Universitas Muhammadiyah Surakarta, 2017)
Temperature plays a major role in detecting climate change brought about by urbanisation and industrialisation. Most climatic impact studies rely on changes in the average values of meteorological variables such as temperature. This paper attempts to study the temporal changes in the mean value of the air surface temperature over Jakarta city during the last century, specifically in the period 1901–2002.The data used in this study were taken from the Jakarta Climatology Station because they are of are good quality, there are extensive records and there is little missing or blank data. Statistic descriptive methods were employed, including a description of the type of probabilistic model chosen to represent the monthly mean air surface temperature time series. The long-term change in temperature was evaluated using the Mann-Kendall trend test method and the statistical linear trend test; the results of these two tests agreed. During the last 100 years, data observations from the station indicate that the monthly mean value of the air surface temperature of Jakarta city has increased at a rate of about 0.152°C decade–1 and has not exhibited variability signals but has changed on average. Based on the linear regression model, the mean value of the air surface temperature over Jakarta city is estimated to reach around 28.5°C in 2050 and 29.23°C in 2100.